A Rare Case of Severe Facial Disfiguration Due to Extranodal NK/T-Cell Lymphoma - Deng H; Yang Q; Shi Z (Journal of Asthma and Allergy)
Huiyi Deng,1,2 Qintai Yang,1,2 Zhaohui Shi1,2 1Department of Otolaryngology-Head and Neck Surgery, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2Department of Allergy, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Zhaohui Shi, Department of Otolaryngology-Head and Neck Surgery, Department of Allergy, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China, Email shizhh35@mail.sysu.edu.cnBackground: Extranodal NK/T-cell lymphoma, nasal type (ENKTCL-NT) is a rare, highly invasive Epstein-Barr virus associated hematological malignant tumor with an unfavorable prognosis. Although ENKTCL-NT has been previously reported, no relevant article has provided an intuitive, progressive series of schematic illustrations of the rapid progression of facial ulcers.Objective: This article reports a serious case of ENKTCL-NT that involved the entire process from onset to death.Case Summary: A 67-year-old man suffered a facial lesion started at the right ala nasi. The wound continued to spread uncontrollably to the nasion and the nasolabial groove. Subsequently, he used an unauthorized external application of herbal medicine, which unfortunately resulted in further expansion of the wound, encompassing the area from the right eyelid to the left inner canthus, extending up to the eyebrow arch, down to the right ala nasi, and deep into the nasal bone over six months. Histopathological analysis of the two biopsies revealed inflammatory necrotic granulation tissue.Conclusion: Nasal extranodal NK/T-cell lymphoma presenting with non-specific symptoms could easily lead to misdiagnosis. It progresses quickly, while adequate, repeated, and multiple spot biopsies for histopathologic examination help confirm the diagnosis.Keywords: ENKTCL-NT, misdiagnose, biopsy, pathology